Sympathomimetic amine compounds and hepatotoxicity: Not all are alike—Key distinctions noted in a short review - Willson, Cyril (Toxicol Rep, 2018)
Sympathomimetic amine compounds are often pooled together and incorrectly assumed to be interchangeable with respect to potential adverse effects. A brief and specific review of sympathomimetic compounds and one instance (i.e., hepatotoxicity) where these compounds have been improperly grouped together is covered. A review of the proposed mechanisms through which known hepatotoxic sympathomimetic agents (e.g., 3,4-methylenedioxymethamphetamine or MDMA, methamphetamine and amphetamine) cause liver injury, along with a corresponding review of in vitro data, interventional data, animal model studies and observational data allow for a comparison/contrast of different agents and reveals a lack of potential toxicity for some agents (e.g., pseudoephedrine, phenylephrine, ephedrine, 1,3-dimethylamylamine, phentermine) in this broad category. Data show that compounds within the broad group of sympathomimetics display divergent pharmacological and toxicological profiles and can be clearly distinguished with respect to liver injury. These data serve as a reminder to clinicians and others, that even small structural differences between molecules can lead to drastically different pharmacological/toxicological profiles and that one should not assume that all sympathomimetic agents are hepatotoxic. Such assumptions could lead to diagnostic errors and incorrect or insufficient treatment.